2009
DOI: 10.1126/science.1175055
|View full text |Cite
|
Sign up to set email alerts
|

Translocator Protein (18 kD) as Target for Anxiolytics Without Benzodiazepine-Like Side Effects

Abstract: Most antianxiety drugs (anxiolytics) work by modulating neurotransmitters in the brain. Benzodiazepines are fast and effective anxiolytic drugs; however, their long-term use is limited by the development of tolerance and withdrawal symptoms. Ligands of the translocator protein [18 kilodaltons (kD)] may promote the synthesis of endogenous neurosteroids, which also exert anxiolytic effects in animal models. Here, we found that the translocator protein (18 kD) ligand XBD173 enhanced gamma-aminobutyric acid-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
279
3
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(297 citation statements)
references
References 26 publications
9
279
3
6
Order By: Relevance
“…The polymorphism plot 10 enables the estimation of V ND by modeling the difference in the HAB and MAB signals across regions of differing target density and is derived from similar principles concerning occupancy studies. 16 This method assumes that the target density is the same for subjects within each genetic group, that the relative regional density is preserved across genetic groups, and V ND is the same for all subjects. These assumptions lead to the following equation, …”
Section: Quantification Of the Non-displaceable Componentmentioning
confidence: 99%
“…The polymorphism plot 10 enables the estimation of V ND by modeling the difference in the HAB and MAB signals across regions of differing target density and is derived from similar principles concerning occupancy studies. 16 This method assumes that the target density is the same for subjects within each genetic group, that the relative regional density is preserved across genetic groups, and V ND is the same for all subjects. These assumptions lead to the following equation, …”
Section: Quantification Of the Non-displaceable Componentmentioning
confidence: 99%
“…Similarly, anxiolytics such as the benzodiazepine alprazolam ameliorate CCK-4-induced panic attacks in healthy volunteers (Zwanzger et al, 2003). Such effects have also been observed in larger samples using XBD173, a ligand of the translocator (TPSO) protein (Rupprecht et al, 2009), which recently has been identified as a possible new treatment target for anxiety (Rupprecht et al, 2010;Nothdurfter et al, 2012). As shown by neuroimaging studies, experimentally induced panic attacks are accompanied by a significant activation of neuroanatomical key areas responsible for the processing of fear and anxiety, such as the amygdala, hippocampus, insula, and the anterior cingulate cortex (ACC) (Schunck et al, 2006;Eser et al, 2009).…”
Section: Introductionmentioning
confidence: 73%
“…Expression of TSPO is upregulated in conditions of neuroinflammation as found in Alzheimer's and Parkinson's disease [5]. TSPO is a secondary binding site for benzodiazepines [6], and small molecules targeting TSPO might become useful in treating anxiety [7]. At the carboxylic terminus, TSPO contains a cholesterol recognition amino acid consensus (CRAC) sequence [8].…”
Section: Introductionmentioning
confidence: 99%